Chemical characteristics analysis of automobile exhaust particles and the method for evaluating its ecological effect. (November 2022) - Cui, Liang; Ni, Hong; Lei, Kun; Gao, Xiangyun; Wang, Xiaonan; Liu, Zhengtao
Abstract: Automobile exhaust has become the main source of atmospheric particulate matter with the increase in the number of automobiles. Automobile exhaust particles (AEPs) discharged into the atmosphere can enter the aquatic environment through atmospheric deposition, rain runoff, leaching, drainage water and urban sewage and further affect aquatic organisms. However, there is no comprehensive theory and method to evaluate the ecological effects of AEPs on aquatic environment. The new European driving cycle (NEDC) and the world harmonized light-duty test cycle (WLTC) were used to analyze the ecotoxicity of AEPs. The SUV gasoline, SUV hybrid and sedan gasoline under WLTC were used for further analysis. The chemical characteristics of AEPs were analyzed, and the ecotoxicity of AEPs on aquatic organisms was studied with Vibrio fischeri and Danio rerio as test organisms. The ecological effect of AEPs was studied through species sensitivity distribution based on interspecies correlation estimation (ICE) models. The results showed that (ⅰ) polycyclic aromatic hydrocarbons (PAHs) were the main organic substances in AEPs. The total concentrations of PAHs in AEPs measured under the NEDC and WLTC were 237.4 and 159.8 mg kg −1, respectively, and the EC50 values for V. fischeri measured under the NEDC and WLTC were 42.02 and 47.05 mg L −1, respectively. (ⅱ) Total heavy metal concentrations in AEPs from SUV gasoline, SUV hybrid, and sedan gasoline were 197.52, 104.86, and 89.68 mg kg −1, respectively, and the LC50 values for D. rerio were 3.22, 4.46 and 5.62 mg L −1 . Cu and Mn were the main toxic heavy metals in AEPs. (ⅲ) The PNEC values of AEPs from SUV gasoline, SUV hybrid and sedan gasoline were 0.57, 0.83 and 1.02 mg L −1, respectively. This exploratory study can provide technical information on water ecological safety assessment for determining the impact of AEPs on the surface water environment and for further improving automobile exhaust emission standards. Graphical abstract: Image 1 Highlights: The chemical characteristics of automobile exhaust particles (AEPs) were analyzed. Heavy metals in AEPs have higher toxicity than organic matter, especially Cu and Mn. ICE models were constructed and to predict the toxicity of AEPs to other organisms. Predict no effect concentration and effect of AEPs on water environment were studied.